2016
DOI: 10.3791/54709
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SCAP <em>N</em>-glycosylation and Trafficking in Human Cells

Abstract: Elevated lipogenesis is a common characteristic of cancer and metabolic diseases. Sterol regulatory element-binding proteins (SREBPs), a family of membrane-bound transcription factors controlling the expression of genes important for the synthesis of cholesterol, fatty acids and phospholipids, are frequently upregulated in these diseases. In the process of SREBP nuclear translocation, SREBP-cleavage activating protein (SCAP) plays a central role in the trafficking of SREBP from the endoplasmic reticulum (ER) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…We found that GBM tumors bearing amplified EGFR, or expressing EGFRvIII, the constitutively active form of the receptor that lacks a portion of the extracellular ligand-binding domain, were greatly dependent on SREBP-1-mediated lipid synthesis and uptake for rapid growth [61]. EGFR/EGFRvIII activates SREBP-1 through upregulation of PI3K/Akt signaling, promoting the expression of ATP citrate lyase (ACLY), acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-coenzyme A desaturase 1 (SCD1) and low density lipoprotein receptor (LDLR) to enhance fatty acid synthesis and cholesterol uptake [13, 60, 61, 80, 83]. …”
Section: Activation Of Scap/srebps In Cancermentioning
confidence: 99%
“…We found that GBM tumors bearing amplified EGFR, or expressing EGFRvIII, the constitutively active form of the receptor that lacks a portion of the extracellular ligand-binding domain, were greatly dependent on SREBP-1-mediated lipid synthesis and uptake for rapid growth [61]. EGFR/EGFRvIII activates SREBP-1 through upregulation of PI3K/Akt signaling, promoting the expression of ATP citrate lyase (ACLY), acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-coenzyme A desaturase 1 (SCD1) and low density lipoprotein receptor (LDLR) to enhance fatty acid synthesis and cholesterol uptake [13, 60, 61, 80, 83]. …”
Section: Activation Of Scap/srebps In Cancermentioning
confidence: 99%
“…To explore whether other factors are critical for SCAP/SREBP trafficking, we investigated the role of glucose-mediated N -glycosylation modification of the SCAP protein, and showed that it was a prerequisite step for SCAP/SREBP trafficking and activation upon cholesterol reduction [2325] . We found that N -glycosylation stabilizes SCAP and reduces its association with Insig-1, allowing SCAP/SREBP movement from the ER to the Golgi (Fig.…”
mentioning
confidence: 99%
“…1). Our study demonstrated that glucose is an essential activator of SCAP/SREBP trafficking, while cholesterol functions as a key inhibitor of this process [2325] .…”
mentioning
confidence: 99%
See 2 more Smart Citations